Model Pembelajaran Pair Check untuk Keterampilan Menulis Siswa SD/MI - Purwitasari, Eva Dewi (BASICA, 2023)
When learning Indonesian in SD/MI, teachers need a learning model to support the smooth running of teaching and learning activities in the classroom. One of the obstacles in learning to write in SD/MI is low interest and writing skills. The Pair Check learning model was chosen by researchers to be used in learning to write in SD/MI so that students can learn independently and responsibly. The research method used by researchers is a qualitative method with a literature study research approach. Data sources in this research include several journals and scientific works according to the research title. The literature is related to the field of pair check learning models and writing skills in SD/MI. Data sources were found in printed and electronic literature. Researchers found ten relevant research journals, but there were three scientific works and journals used. The literature study was carried out by the author looking for scientific works and research journals that were relevant to the research title. Based on the results of literature studies in three journals, it can be concluded that elementary/MI students' writing skills have improved by using the Pair Share learning model. Improvement is not only in student learning outcomes but also student activity and interest. So, implementing the Pair Share learning model can be a solution and a varied learning model and provide innovation to teachers when implementing writing lessons. Apart from that, this learning model is also expected to be able to improve students' writing learning outcomes in SD/MI.